2009
DOI: 10.2746/042516409x441929
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with equine gastric ulceration syndrome (EGUS) in 201 horses in Denmark

Abstract: This study has confirmed that components of the diet, readily modifiable, may have an important impact on the risk of EGUS in the nonracehorse. Differences in the multivariable models produced for all ulcers and nonglandular ulcers support differences in the aetiology of ulcers in different locations of the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
142
3
21

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 174 publications
(171 citation statements)
references
References 32 publications
5
142
3
21
Order By: Relevance
“…Intermittent access to water increases the risk of EGUS as it has been shown that horses without access to water in their paddock are more than 2.5 times more likely to have EGUS ≥ 2/5 than horses with constant access to water 24. This was the case for both ESGD or EGUS in all parts of the stomach.…”
Section: Epidemiologymentioning
confidence: 98%
See 4 more Smart Citations
“…Intermittent access to water increases the risk of EGUS as it has been shown that horses without access to water in their paddock are more than 2.5 times more likely to have EGUS ≥ 2/5 than horses with constant access to water 24. This was the case for both ESGD or EGUS in all parts of the stomach.…”
Section: Epidemiologymentioning
confidence: 98%
“…Of those available, significant associations have been shown between ESGD and individual trainers, a metropolitan yard location (horses trained in urban areas were 3.9 × more likely to have gastric ulcers), a lack of direct contact with other horses, solid barriers instead of rails, and talk rather than music radio in the barn 23. Straw feeding and a lack of access to water in the paddock have been associated with an increased risk of EGUS in general 24. Further large scale work is required to better understand the epidemiologic factors which influence disease development, particularly EGGD which is largely unstudied at this point in time.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations